Recent advances in the management of diabetic retinopathy. Issue 8 (August 2019) - Dulull, Nabeela; Kwa, Faith; Osman, Narin; Rai, Uma; Shaikh, Bilal; Thrimawithana, Thilini R.
Highlights: Current treatment for diabetic retinopathy targets late stages of the disease. Promising novel drug candidates include integrin antagonists and Tie-2 inhibitors. Novel sustained release drug delivery systems will be available in the near future. Emerging therapies will target oxidative stress and epigenetic pathways. There is a need to target multiple pathways at the early stages of the disease. Teaser: Diabetic retinopathy is the leading cause of blindness in young adults. Current treatments target late-stage disease symptoms. This review highlights the need for new therapies that target early stages of the disease. Abstract : Diabetic retinopathy (DR) is a microvascular complication of diabetes and is the leading cause of vision loss in people with diabetes. The current treatments do not target early stages of disease or impede disease progression. Therefore, the identification of new therapeutic targets, the development of novel therapies targeting early stages of the disease and accurate models that simulate pathological characteristics of this disorder are crucial. This review provides an overview of the pathological mechanisms underlying the development of DR, highlighting the recent advances in current and emerging treatments for DR.